ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN MINAT BELI KONSUMEN DIBEDAR RESTO DAN KAFE DALAM PERSFEKTIF EKONOMI ISLAM - Faturohman, Adji; Jum’an (Sebi : Studi Ekonomi dan Bisnis Islam, 2024)
This study uses a quantitative research approach. The type of research used in this research is a type of field research, with a sample of 47 respondents. The method used in the analysis is with the help of google forms and for data processing using SPSS statistics 25 Partially the income variable has a significant effect on students' saving awareness at the Mini Bank Laboratory. Thus it can be concluded that the first hypothesis which states that there is an effect of the income variable on saving awareness and is significant, H1 is accepted and Ho is rejected. Partially, the financial literacy variable has a significant effect on students' saving awareness at the Mini Bank Laboratory. Thus it can be concluded that the second hypothesis which states that there is an effect of the financial literacy variable on saving awareness and is significant that H2 is accepted and Ho is rejected. Simultaneously there is an influence between income and financial literacy on students' awareness of saving at the Laboratory of the Mini Bank of the Islamic Institute of Sultan Muhammad Syafiuddin Sambas, which is indicated by the Fcount> F table of 16.347>3.209 while the significance level is smaller than 0.05, which is 0. 000<0.05 so that the effect is 42.6%. Thus it can be concluded that income and financial literacy have a positive effect on saving awareness.